Interpretation of Magnetic Anomalies by Simple Geometrical Structures Using the Manta-Ray Foraging Optimization - Ben, Ubong C.; Ekwok, Stephen E.; Akpan, Anthony E.; Mbonu, Charles C.; Eldosouky, Ahmed M.; Abdelrahman, Kamal; Gómez-Ortiz, David (Frontiers in Earth Science, 2022)
In this paper, a geophysical strategy based on the recently proposed Manta-Ray Foraging (MRF) Optimization algorithm is adapted and presented for the blind computation of depth/shape defining parameters from magnetic anomalies due to buried geo-bodies. The model parameters deciphered are the coefficient of amplitude (K), buried structure’s origin (x0), the depth (z), magnetization angle (α), and a shape factor (q). After detailed and piecewise design, the new inversion tool is originally trial-tested on anomaly data generated synthetically. The uncorrupted version of the test data is first analyzed, then - it is corrupted with noise varied at 5, 10, 15, and 20% corruption levels. Thereafter, it is experimented with magnetic profiles taken from exploration fields in the United States, Peru, and Egypt. From the evaluation of results obtained, the new procedure is observed as exhibiting outstanding stability and flexibility especially with noisy dataset and notable efficiency in the quantitative resolution of magnetic inversion problems. The results obtained for the field cases are also mostly consistent especially when compared with background results from similar studies conducted with other methods; further affirming the new tool as reliable for the geophysical investigation of buried minerals.